Metal-organic framework-based nanomaterials for CO2 storage: A review - Do, Ha Huu; Rabani, Iqra; Truong, Hai Bang (Beilstein Journal of Nanotechnology, 2023)
The increasing recognition of the impact of CO2 emissions as a global concern, directly linked to the rise in global temperature, has raised significant attention. Carbon capture and storage, particularly in association with adsorbents, has occurred as a pivotal approach to address this pressing issue. Large surface area, high porosity, and abundant adsorption sites make metal-organic frameworks (MOFs) promising contenders for CO2 uptake. This review commences by discussing recent advancements in MOFs with diverse adsorption sites, encompassing open metal sites and Lewis basic centers. Next, diverse strategies aimed at enhancing CO2 adsorption capabilities are presented, including pore size manipulation, post-synthetic modifications, and composite formation. Finally, the extant challenges and anticipated prospects pertaining to the development of MOF-based nanomaterials for CO2 storage are described.
Keywords: CO2 storage; metal-organic frameworks; nanomaterials; open metal sites; pore size